The Effect of Using Pictionary Games on Improving Speaking Skill of Grade Eighth Students in SMP YPAK PTPN 3 Gunung Para Dolok Merawan (Bilingual : Jurnal Pendidikan Bahasa Inggris, 2025)
This study aims to determine the effect of using Pictionary game in improving the speaking skill of students in class VIII of SMP YPAK PTPN 3 Gunung Para Dolok Merawan. This research used quantitative method with true-experimental method approach. The population of this study were VIII grade students consisting of 3 classes consisting of 134 students and the sample of this study were 86 students consisting of two classes. The data collection techniques used were pre-test and post-test. Data analysis techniques using SPSS version 27.0. The results showed that tcount (5.205) > ttable (1.681) at the significance level α = 0.05 with degrees of freedom (df) = 42. This means that H0 is rejected and Ha is accepted. Based on evidence from the research results, the post-test has a higher value than the pre-test. From these results, it is concluded that there is a significant difference in improving students' speaking skill before and after being given treatment by using Pictionary game media as learning media. Therefore, researchers believe that the use of Pictionary Game can be used to improve the speaking skill of students in grade VIII of SMP YPAK PTPN 3 Gunung Para Dolok Merawan. Because the use of Pictionary Game as a learning media for English speaking skill is very effective. Pictionary game media has a positive influence on students' speaking skill by increasing students' creativity and involvement in the learning process. Therefore, Pictionary game can be considered as an effective and fun teaching strategy to improve speaking skill